The global cryosphere : past, present, and future - Barry, Roger G.; Gan, Thian Yew. (Cambridge: Cambridge University Press, 2011)
"This is the first textbook to address all the components of the Earth's cryosphere - all forms of snow and ice, both terrestrial and marine. It provides a concise but comprehensive summary of snow cover, glaciers, ice sheets, lake and river ice, permafrost, sea ice and icebergs - their past history and projected future state. It is designed for courses at upper undergraduate and graduate level in environmental science, geography, geology, glaciology, hydrology, water resource engineering and ocean sciences. It also provides a superb up-to-date summary for researchers of the cryosphere. The book includes an extensive bibliography, numerous figures and color plates, thematic boxes on selected topics and a glossary. The book builds on courses taught by the authors for many decades at the University of Colorado and the University of Alberta. Whilst there are many existing texts on individual components of the cryosphere, no other textbook covers the whole cryosphere"--
Introduction -- Part I. The terrestrial cryosphere. Snowfall and snov cover ; Avalanches ; Glaciers and ice caps ; Ice sheets ; Frozen ground and permafrost ; Freshwater ice -- Part II. The marine cryosphere. Sea ice ; Ice shelves and icebergs -- Part III. The cryosphere past and future. The cryosphere in the past ; The future cryosphere : impacts of global warming -- Part IV. Applications. Applications of snow and ice research.
Includes bibliographical references and index.
Keywords: Cryosphere -- History; Cold regions -- History; Glaciers -- History; Ice sheets -- History